Value change in the period of transition: A snap shot from Croatia - Jerneić, Željko; Šverko, Branimir (1999)
The values of people in Eastern and Central Europe in general, and their values related to work in particular, have received an increased attention during this decade. Privatization and transition to market economy, processes that have radically altered the conditions of employment, have stimulated interest in surveys addressing the question of possible changes in work-related values. This paper analyses the value change in Croatian students during the transition period of 1990s. The instrument used was the Values Scale, a multi-scale instrument developed within Work Importance Study (1). We administered the Values Scale to a representative sample of Croatian university students in spring 1998 (N=800). These data are compared with the comparable data gathered in the beginning of transition period, in spring 1994 (N=298), as well as with the original WIS data collected before the transition, in 1983 (N=348). The comparisons showed that two groups of values underwent significant change during the transition period: utilitarian values and indi-vidualistic values increased in importance. The increase of the utilitarian values we attribute to a changed economic system. The new system promotes entrepreneurship and economic efficiency and thus lays more emphasis on the values stressing upward mobility, material suc-cess and prestige. The increased emphasis on individualistic values we attribute to a general post-socialist move away from collectivism.
Projekt MZOS
ENG